La Etnografía Colaborativa en la formación en investigación en Ciencias de la Educación - Heras Monner Sans, Ana Inés (2018)
Fil: Fil: Heras Monner Sans, Ana Inés. Universidad Nacional de San Martín. Buenos Aires; Argentina